A Passage to England: Nirad C. Chaudhary: Exploring the Impact of Hegemony on Friendship Formation in Colonial India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper deals with the notions of E M. Forester’s criticism how hegemony inhibits the formation of personal ties between local indigenous people and Anglo-Indian people. The narrator presents this idea at the beginning, when Mahmoud Ali and Hamidullah ask whether or not an Englishman can have friends (Forster, 1924. 33). On the final page, Forster addresses this hypothesis by saying, No, not yet.... No, there isn't (Forester 316). This means that, for strategic, hegemonic and prejudicial purposes, any efforts to develop friendships are impossible under the British occupation. In posing a variety of pitfalls, while individuals attempt to interact in colonial India, Forster’s case against imperialism is very simple and compelling.